Does Cheaper, Faster, or Better Imply Sooner in the Timing of Innovation Decisions? - Lippman, Steven A.; McCardle, Kevin F. (Management Science, 1987)
A common myth/conception, based upon the notion of increasing returns to scale in R&D activity, is that large firms account for a disproportionate share of innovations. In this paper we consider three types of informational returns to scale (cheaper, faster, and better) and examine the impact of each on the timing of the firm's innovation decision. Contrary to popular conception, the decision is made later when information is cheaper, and the change in timing is unsignable in the case of faster arrival of information. Only more accurate (better) information leads to earlier decisions.